Psychospiritual Nursing Interventions In Reducing Students' Anxiety Levels - Suyanto, Suyanto; Astuti, Sri Lestari Dwi; Rohimah, Yenni Tutu (International Journal Labs, 2025)
Anxiety is often experienced by students in their lives at the Islamic boarding school because it is very different from life outside the Islamic boarding school where a child is free to do activities and all needs are still handled by their parents. The anxious condition experienced will interfere with the students' learning process. Various ways of handling to reduce anxiety include using self-healing techniques combined with dhikr so that emotions and anger can be controlled. The Butterfly Hug method that creates suggestions, comfortable and calm conditions. To make these conditions more optimal, the researcher combined it with dhikr as a method of remembering and getting closer to Allah SWT which has never been studied. The design of this study is a quasi-experimental design with a pre and post without control group design. All 27 male students were used as samples. While the research instrument used the SCAS (Spence Children's Anxiety Scale) anxiety questionnaire. Before the administration of the combination therapy of Butterfly Hug and Dhikr, the level of anxiety was mild to high. After the administration of the combination therapy of Butterfly Hug and Dhikr, there was a change, namely the most was the level of moderate anxiety experienced by students. The results of the Wilcoxon Test obtained a p value of 0.000. Thus, it means that there is an effect of the combination therapy of Butterfly Hug and dhikr on anxiety in students at the Al Muslimun Islamic Boarding School, which was rejected. There is an effect of the combination therapy of Butterfly Hug and dhikr on reducing anxiety in students at the Al Muslimun Islamic Boarding School, Durenan Sidorejo Magetan. It is hoped that Butterfly Hug and Dhikr can be used as one of the therapies in overcoming anxiety that can be done independently by students at the Islamic boarding school.